Fast DBF for conformal arrays based on 2D Fourier decomposition - Yuan Yao; Guangxin Wu (The Journal of Engineering, 2019)
Digital array radars with conformal arrays are attractive for platforms with limited installation space such as aircraft and unmanned aerial vehicles. Low-complexity digital beamforming (DBF) scheme is of great importance for conformal arrays with arbitrary geometry for real-time applications. This study presents two kinds of two-dimensional (2D) Fourier bases for the orthogonal decomposition of arbitrary array manifold. The sampling matrix (2D Fourier spectra) can be obtained from the 2D DFT of the array calibration data, facilitating fast DBF scheme for conformal arrays. Moreover, the second 2D Fourier basis can be used to rotate a function on [inline-formula]. The modelling accuracy and complexity of different 2D Fourier representations are compared by numerical results and the rotation of functions on [inline-formula] is demonstrated.